Enhanced Thermoelectric Performance of c-Axis-Oriented Epitaxial Ba-Doped BiCuSeO Thin Films - Dachao Yuan; Shuang Guo; Shuaihang Hou; Yuejin Ma; Jianglong Wang; Shufang Wang (Nanoscale Research Letters, 2018)
Abstract We reported the epitaxial growth of c-axis-oriented Bi1−x Ba x CuSeO (0 ≤ x ≤ 10%) thin films and investigated the effect of Ba doping on the structure, valence state of elements, and thermoelectric properties of the films. X-ray photoelectron spectroscopy analysis reveal that Bi3+ is partially reduced to the lower valence state after Ba doping, while Cu and Se ions still exist as + 1 and − 2 valence state, respectively. As the Ba doping content increases, both resistivity and Seebeck coefficient decrease because of the increased hole carrier concentration. A large power factor, as high as 1.24 mWm−1 K−2 at 673 K, has been achieved in the 7.5% Ba-doped BiCuSeO thin film, which is 1.5 times higher than those reported for the corresponding bulk samples. Considering that the nanoscale-thick Ba-doped films should have a very low thermal conductivity, high ZT can be expected in the films.